Species diversity driven by morphological and ecological disparity: a case study of comparative seed morphology and anatomy across a large monocot order. Issue 1 (26th October 2016) - Benedict, John C.; Smith, Selena Y.; Specht, Chelsea D.; Collinson, Margaret E.; Leong-Škorničková, Jana; Parkinson, Dilworth Y.; Marone, Federica
Abstract : The banana and ginger group, order Zingiberales, comprises of exceptionally diverse, primarily tropical, plants. Within Zingiberales, the ginger family (Zingiberaceae) is unique in being not only the most species-rich but also the most disparate in terms of their morphology and anatomy, and the only group with a substantial number of species in temperate environments. Multiple radiations into temperate habitats were found to not be driven by morphological change, but instead may point to a genetic plasticity in the family that provided opportunities for speciation events not found anywhere else in the order. Abstract: Phenotypic variation can be attributed to genetic heritability as well as biotic and abiotic factors. Across Zingiberales, there is a high variation in the number of species per clade and in phenotypic diversity. Factors contributing to this phenotypic variation have never been studied in a phylogenetic or ecological context. Seeds of 166 species from all eight families in Zingiberales were analyzed for 51 characters using synchrotron based 3D X-ray tomographic microscopy to determine phylogenetically informative characters and to understand the distribution of morphological disparity within the order. All families are distinguishable based on seed characters. Non-metric multidimensional scaling analyses show Zingiberaceae occupy the largest seed morphospace relative to the other families, and environmental analyses demonstrate that Zingiberaceae inhabit both temperate and tropical regions, while other Zingiberales are almost exclusively tropical. Temperate species do not cluster in morphospace nor do they share a common suite of character states. This suggests that the diversity seen is not driven by adaptation to temperate niches; rather, the morphological disparity seen likely reflects an underlying genetic plasticity that allowed Zingiberaceae to repeatedly colonize temperate environments. The notable morphoanatomical variety in Zingiberaceae seeds may account for their extraordinary ecological success and high species diversity as compared to other Zingiberales.